ANALYSIS OF FACTORS AFFECTING INCOME FARMERS PALM MEMBERS KUD (Koperasi Unit Desa) MARSAWA VILLAGE SUBDISTRICT BENAI REGENCY KUANTAN SINGINGI - SASMITA, SYAFRIANI; Johan, Rina Selva; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACKThis study aims to describe the level of welfare of the farmers self Village Unit Cooperatives (KUD) Trans in palm oil farming and calculate the level of farm income non-oil palm farmer cooperatives. The study was conducted using a survey method, the 33 non-farmers as a sample. The choice of location studies done deliberately. The data collected in this study is primary data and secondary data. Sampling method is done deliberately. The level of empowerment of farmers in oil palm cultivation was measured using scores and income calculated using the formula income. The results showed differences in the income of farmers in the farming of palm oil as measured by various factors that may affect farmers' income, either directly or indirectly. With the help of an institutional form of cooperation, facilitate the farmers in meeting the needs and the things that can facilitate their activities to improve the performance and the farmer's produce. Examples of research results obtained average farmer's income of Rp 12 million per year with an average the TBS production of Rp. 43872.73 kg per year and the average amount of fertilizer per tahunyang issued Rp. 3,497,548.48 per year.Keywords: Cooperative Village Unit, Revenue, Palm Oil